Johnson's illustrated & embellished steel plate map of the world on Mercator's Projection, compiled from the latest & most authentic sources exhibiting the recent Arctic and Antarctic discoveries & explorations / engraved & published by D. Griffing Johnson, 80 Nassau St. New York. 1847. Entered according to act of congress . 1846 by D. Griffing Johnson . New York. - Johnson, D. Griffing (D. Griffing Johnson, 1847)
Relief shown by hachures. Includes illustrations and views around margins. Color; 1:15,000,000